2021
DOI: 10.3390/cancers13235978
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Analysis in a Cohort of Parkinson’s Disease Patients and Clock-Modified Colorectal Cancer Cells Reveals Common Expression Alterations in Clock-Regulated Genes

Abstract: Increasing evidence suggests a role for circadian dysregulation in prompting disease-related phenotypes in mammals. Cancer and neurodegenerative disorders are two aging related diseases reported to be associated with circadian disruption. In this study, we investigated a possible effect of circadian disruption in Parkinson’s disease (PD) and colorectal cancer (CRC). We used high-throughput data sets retrieved from whole blood of idiopathic PD (IPD) patients and time course data sets derived from an in vitro mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 160 publications
(208 reference statements)
0
11
0
Order By: Relevance
“…reported among patients as compared to the healthy control groups 99 . This highlight potential implications of spaceflights in neurodegeneration and further research in this direction will be needed.…”
Section: Ndufs2mentioning
confidence: 95%
“…reported among patients as compared to the healthy control groups 99 . This highlight potential implications of spaceflights in neurodegeneration and further research in this direction will be needed.…”
Section: Ndufs2mentioning
confidence: 95%
“…Recently, a time course analysis using human colorectal cancer (CRC) cells with distinct clock phenotypes pointed to a link between cancer and neurodegenerative diseases involving the circadian system, and suggested the differential enrichment of genes involved in HD, AD and PD ( Yalcin et al, 2020 ). In a follow-up study, the KO of core-clock genes in CRC cell lines was shown to disrupt rhythmic expression of cancer and neurodegeneration-related genes and led to similar alterations at the mean gene expression level, as observed in a cohort of PD patients compared to healthy controls ( Yalcin et al, 2021 ). Circadian disturbances are among the earliest symptoms of neurodegenerative diseases such as HD, AD, and PD, and malfunctioning in the molecular mechanisms of the circadian system is thought to play a pivotal, and possibly even causal, role in their pathological development ( Hood and Amir, 2017b ; Carter et al, 2021 ).…”
Section: Making Biological Time: the Molecular And Neural Circuits Me...mentioning
confidence: 80%
“…In a recent bioinformatics study pointing to molecular clock dysfunction in PD ( Yalçin et al, 2021 ), PD patients exhibited weaker correlations in the expression of clock genes than in age and sex matched controls. In a normally functioning cell or organism, expression of clock genes is tightly ruled by intricated feedback loops and entrained by the master clock in the SCN.…”
Section: Making Biological Time: the Molecular And Neural Circuits Me...mentioning
confidence: 99%
“…HCT116 core-clock KO cell lines were generated as previously described [ 42 , 43 ]. In short, HCT116 WT cells were transfected with CRISPR-Cas9 plasmids and guide RNAs targeting core-clock genes BMAL1 , PER2 or NR1D1 .…”
Section: Methodsmentioning
confidence: 99%